Optimizing E-Government through E-Buddy in Candipari Village Administration: Optimalisasi Pemerintahan Elektronik melalui E-Buddy dalam Administrasi Desa Candipari - Kustianingsih, Silvana Hari; Choiriyah , Ilmi Usrotin (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The advancement of information technology has driven the transformation of public administration toward digital governance to ensure efficiency, transparency, and accountability in government performance. Specific Background: In Sidoarjo Regency, the E-Buddy application serves as a medium for electronic correspondence management, aligning with the e-Government policy framework. However, its implementation at the village level, particularly in Candipari Village, remains suboptimal due to limited human resources and infrastructure. Knowledge Gap: Previous studies have not sufficiently examined how the Government-to-Government (G2G) model operates through E-Buddy at the grassroots level. Aims: This study aims to analyze the implementation of the E-Buddy system in managing incoming and outgoing letters in Candipari Village based on Edward III’s implementation theory. Results: Findings reveal that while E-Buddy improves document accessibility and communication flow, challenges persist in communication clarity, training, and system reliability. Novelty: This research provides an in-depth exploration of digital governance at the village level by integrating G2G interaction within a local administrative framework. Implications: Strengthening human resource capacity, infrastructure, and clear SOPs is crucial for sustaining e-Government initiatives in rural governance. Highlights: E-Buddy enhances administrative transparency and efficiency. Human resource and communication gaps hinder full implementation. Provides new insight into G2G digital governance at the village level. Keywords: E-Government, E-Buddy, Government-to-Government, Public Administration, Digital Archive